EFFECT OF VARIOUS SUBSTRATE ON THE YIELD AND QUALITY OF RADISH (Raphanus sativus) - Ahmed, Ghazi Othman; Nadir, Hawrez Ali; Abdulla, Nakhshin Omer (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2023)
This study was carried out in field of Sulimani Polytechnic University, Halabja Technical College of Applied Sciences, Department of Agriculture Project Management, in 2021-2022 to test of different types of peat moss (Latvia, Iraq, Turkish, Germany, and Holland), and various level of peat moss (0,2.5, and 5 percent) on the growth and yield of radish plant (Raphanus sativus). This experiment was designed complied random block design (RCBD), with fifteen treatments and three replications. As results, the morphological properties (chlorophyll, leave tall, leave weight before and after dry, root tall, root diameter, root weight before and after dry, root and leaves dry, root and leaves water content) showed that the statistically not significant different between treatments. However, the highest chlorophyll was taken from treatment Iraq+ level 5 percent (23.967). Also, the highest leave tall, leave weight before dry, root dimeter, root tall, and root weight before and after dry was obtained from treatment that consist of Germany peat moss + level 5 percent (18.4 cm, 22.2 g, 8.4 cm, 39.157 mm, 58.433 g, 2.333 g) respectively. Also, the maximum of leaves weight (g) after dry was obtained from the treatment of Holland peat moss + level 5 percent (2,6 g). Furthermore, the interaction between treatment showed statically not significant different between them. Thus, application of peat moss is important to cultivation of radish and organic crop production. Even so, recommendation to the farm and scientist to use higher level that the level used in this study.